Material acts in everyday Hindu worlds - Flueckiger, Joyce Burkhalter (SUNY series in Hindu studies, 2020)
"Over the last few decades, there has been a renewed intellectual energy in religious studies around material culture; however, most of the attention has been focused on the ways humans use material objects and what specific materials reflect about humans. In Material Acts in Everyday Hindu Worlds, Joyce Burkhalter Flueckiger shifts the focus from human agents to material ones, which have an effect, or cause something to happen, that may be beyond what a human creator of the material intended. Analyzing materials from three regions where she has conducted extensive fieldwork, Flueckiger begins with Indian understandings of the agency of ornaments that have the desired effects of protecting women and making them more auspicious. Subsequent chapters bring in examples of materiality that are agentive beyond human intentions, from a south Indian goddess tradition where female guising transforms the aggressive masculinity of men who wear saris, braids, and breasts, to the presence of cement images of Ravana in Chhattisgarh, which perform alternative theologies and ideologies to those of dominant textual traditions of the Ramayana epic, in which Ravana is destroyed by the god Rama. Deeply ethnographic and accessibly written, Material Acts in Everyday Hindu Worlds expands our understanding of specific religious practices in India as well as the parameters of religion more broadly"--